Uma heurística de desenvolvimento de tecnologia comportamental para redução do estigma direcionado a estudantes com transtorno do espectro do autismo - Perkoski, Izadora Ribeiro (Universidade Federal de São Carlos, 2021)
Technology can be defined as a way to solve important human problems. Behavioral technology, specifically, is applying the scientific findings of Behavior Analysis to solve socially relevant behavioral problems. Despite strengthening itself as a scientific perspective of Psychology, being a well-defined field of knowledge, and with a prolific production of data, there are still few investigations about the transposition of behavioral-analytic science to technology development. The aim of this thesis is to propose a heuristic for the development of behavioral technologies and demonstrate its application to a complex problem in the domain of Special Education. As specific objectives, we seek to define, based on the literature, what behavioral technology is; Propose and describe a heuristic for the creation of behavioral technology; Describe the application of the proposed heuristic in the design of a game manual to reduce stigma through structured contact between children with and without ASD. Several methods were applied at each stage of the research. The heuristic was described based on the specialized literature, and a systematic procedure to develop behavioral interventions was created. Evidence was collected using systematic review, and the operational definition process also sought to follow a procedure replicable by other researchers. The development process of the behavioral intervention was described step-by-step, allowing for replication and future iterations. This thesis is structured in three main chapters, two additional chapters, and the created game manual presented as an appendix. The three main chapters go from the theoretical definition of behavioral technology and the functional description of the behaviors that make up the behavior of the behavior analyst in the development of technology, in Chapter 1, through the proposal of a heuristic procedure for the construction of behavioral technologies, in Chapter 2, ending with the demonstration of the application of this heuristic to a natural environment problem (the facilitation of non-stigmatizing interactions between children with and without ASD), in Chapter 3. The two additional chapters are the results of collecting the necessary information for the construction of the game proposed in Chapter 3: a conceptual study of stigmatizing behavior and a proposed operational definition based on empirical literature (Additional Chapter 1); and a systematic review of the literature, evaluating the tools with the strongest evidence in reducing stigma in the school environment (Additional Chapter 2). It is expected that the adoption of a structured procedure for the development of behavioral interventions, when applied to the context of combating the stigmatization of children with ASD, will help in the production of future effective intervention tools. Despite the description of a systematic way of creating the tool, it is important to emphasize that the detailed description of the process of developing technology cannot replace its empirical evaluation. Thus, we hope that in the future efficacy and generalization tests, hampered by the SarsCov2 virus pandemic, can be conducted. Empirical evaluation is indispensable for characterizing a behavioranalytic technology as such.
An heuristic for developing behavioural technology for the reduction of stigma towards students with autism spectrum disorder
Keywords: Tecnologia comportamental; Análise do comportamento; Autismo; Heurística; Inclusão; Jogos educacionais; Behavioral technology; Behavior analysis; Autism; Heuristic; Inclusion; Educational games; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::TECNOLOGIA EDUCACIONAL; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::ENSINO E APRENDIZAGEM NA SALA DE AULA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL